The Relationship between Vitamin D Levels and Muscle Mass in Obese Children - Hefira Rosadiani; Wistiani; Galuh Hardaningsih (Archives of The Medicine and Case Reports, 2023)
Obesity can result in the secretion of proinflammatory mediators, which can result in vitamin D deficiency and decreased muscle mass. Good muscle mass is necessary for a good quality of life in obese children. This study aimed to determine the relationship between vitamin D levels and muscle mass in obese children. The average muscle mass in obese children is 15.04 kg. As many as 24.4% of children have normal muscle mass levels, while 75.6% of obese children have low muscle mass. This study is an analytic observational study with a cross-sectional approach. A total of 86 research subjects participated in this study. Measurement of muscle mass and vitamin D levels was carried out in this study. Data analysis was performed using SPSS version 20 using univariate and bivariate methods. The average vitamin D level was 26.65 ng/mL. As many as 69.8% of obese children had normal vitamin D levels, while 30.2% had low levels of vitamin D. In conclusion, there is no relationship between vitamin D levels and muscle mass in obese children.